Binding Social Capital: Study of Bahrul Ulum Barokah Sejahtera Micro Waqf Bank Customers: Study of Bahrul Ulum Barokah Sejahtera Micro Waqf Bank Customers - Fitrianita, Titi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
This study examines the social capital that ties Bahrul Ulum Barokah Sejahtera Micro Waqf Bank (Bank Wakaf Mikro, BWM) borrowers together. The effective repayment of money lent by BWM clients was the impetus for this study. Refunds were delayed during the COVID-19 outbreak because Santri students)—the primary source of income for small and medium company owners near Islamic boarding schools—were sent home by official guidelines. When students returned to study at pesantren during the New Normal period, pesantren leader imposed limitations on small- and micro-business owners’ conduct, raising the risk of loan default. However, this missed payment did not happen, and even 80% of the money in bankruptcy has been recovered. This condition motivates researchers to investigate the many conditions that may exist further. This study employs a mixed method sequential methodology by distributing questionnaires to 95 respondents using random sampling and interviews with seven informants selected purposely. This study applies Robert D. Putnam’s social capital binding theory, enhances the analysis, and examines this social capital by finding networks, norms, and trust among BWM clients. According to the findings of this study, bridging social capital is the factor consumers depend on the most to keep up with their repayment responsibilities to BWM. Geographic homogeneity, education, income, and religion are all essential factors in forming binding social capital to return loan funds.